Phytoplankton abundance and diversity in a fish pond and its adjacent waters in Pinabacdao, Samar. - Pontejos, Guinevere Paul M. (Guinevere Paul M. Pontejos, 2019)
This study was conducted in a privately-owned fish pond in an estuary of Pinabacdao, Samar to determine the abundance and diversity of the phytoplankton community in the fish pond and in its adjacent waters. Physico-chemical parameters, and concentrations of nitrates, phosphates and chlorophyll-a in the study sites were measured. Phytoplankton samples were collected using a bucket and plankton net (mesh size: 20-um; aperture diameter: 30 cm; length: 0.5 m). The results of the study show that the fish pond was less diverse (H'=1.78) than the adjacent waters (H'=2.08). A total of 55 phytoplankton genera were identified in the sampling sites; 37 genera were identified inside the fish pond while 49 genera were found its adjacent waters. Diatoms were the most abundant in both sides. Moreover, the cell densities of the fish pond were significantly lower than the adjacent waters, with the values of 5x10 raised to the power of 3 cells/L and 21 x10 raised to the power of 3 cells/L, respectively. Both nitrate concentrations of the sampling sites exceeded the accepted values, while phosphate concentrations did not. Additionally, chrorophyll-a concentrations inside the fish pond were lower compared to the waters outside. In comparison with the fish pond in Carigara, Leyte and its adjacent waters, the phytoplankton community in Pinabacdao, Samar was found to be more diverse. Recent trends in aquaculture incorporate the phytoplankton community for water quality management; hence, the phytoplankton data and results generated in this study could be used to determine the water quality of the fish pond waters and develop better pond management strategies.